An empirical study on the effect of e-service quality on online customer satisfaction and loyalty - Sihombing, Lenti; Pratminingsih, Astuti; Yazid, Mohd Faizun Mohamad (International Journal of Psychosocial Rehabilitation, 2020)
Acceptance level of e-commerce and online transactions have been tremendously increased. The acceptance rate increases every year and slowly the usage of it become wider covering all aspects of life. This research is about the role of e-service quality towards customer satisfaction and customer loyalty. Customer satisfaction is also tested as mediator in between e-service quality towards customer loyalty. Both play important roles in order to serve customer better and gain the advantages over the competition. The quantitative approached used in this research with a total of 220 respondents from all type of ages who have experienced using the e-services. This research used questionnaire with 25 items using 5 points Likert-scales. Respondent was among the public based on purposive sampling. Overall it took 5 days for the researchers to complete the process. The results indicate that e-service quality and customer satisfaction is positively related to customer loyalty. Both e-service quality and customer satisfaction are important roles as predictors. At the same time customer satisfaction is also show positive results as a control variable between e-service quality and customer loyalty. Such results are important to be used and practiced by the industry plays especially those who are new in the market in order to compete with the largest players. Customer today is very complicated and yet knowledgeable and due to that information and know-how is crucial as part of the strategy in winning the completion among industry members.